2001
DOI: 10.1089/15258160152509163
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Production of Dendritic Cells from Human Blood Monocytes for Therapeutic Use

Abstract: Dendritic cells (DC) are professional antigen-presenting cells that are promising adjuvants for clinical immunotherapy. Methods to generate in vitro large numbers of functional human DC using either peripheral blood monocytes or CD34(+) pluripotent hematopoietic progenitor cells have been now developed. For this purpose, their in vitro production for further clinical use need to fit good manufacturing practice (GMP) conditions. In the present review, we give our experience of such a procedure: it includes coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…21,42 CD40-activated B cells have an important advantage for this purpose in that they can be readily expanded in vitro to a relatively large numbers (Figure 1), whereas, in contrast, monocytes differentiating in vitro into DCs do not undergo cell division. 22 Cryopreserved CD40-activated B cells also retain their APC function on thawing and are relatively cost-effective to produce. 26,27 In addition, because B cells stimulated with t-CD40-L cells or recombinant sCD40-L were equally effective at generating alloantigen-specific Treg, the use of sCD40-L may significantly improve the clinical applicability of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,42 CD40-activated B cells have an important advantage for this purpose in that they can be readily expanded in vitro to a relatively large numbers (Figure 1), whereas, in contrast, monocytes differentiating in vitro into DCs do not undergo cell division. 22 Cryopreserved CD40-activated B cells also retain their APC function on thawing and are relatively cost-effective to produce. 26,27 In addition, because B cells stimulated with t-CD40-L cells or recombinant sCD40-L were equally effective at generating alloantigen-specific Treg, the use of sCD40-L may significantly improve the clinical applicability of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, DCs are relatively rare in peripheral blood and are usually derived from apheresis or marrow sources, including monocytes. 22,23 Further, DCs are not homogeneous and include multiple subsets with different functional capacities. 24 Finally, there is no effective way to expand human The online version of this article contains a data supplement.…”
mentioning
confidence: 99%
“…Others have studied the importance of AS for the generation of optimally immunostimulatory DCs. Garderet et al [22] found significantly higher expression of CD40, CD54 and CD86 on immature DCs generated in RPMI-1640 with 10% AS than in DCs generated in SFM. This difference was augmented after maturation for 2 days.…”
Section: Discussionmentioning
confidence: 97%
“…CD14+ cells, non-proliferative DC precursors, are obtained from leukapheresis procedures, buffy coat preparations, or peripheral blood draws [21][22][23]. In the laboratory, CD14+ monocytes are purified from blood using elutriation procedures [24,25], immunomagnetic purification [7] or adherence [26,27] steps. In some cases, DCs are derived from a proliferative CD34+ cell population and are obtained from the peripheral blood following mobilization using G-CSF (granulocyte colony stimulating factor) [28] and/or GMCSF (granulocyte monocyte colony stimulating factor) infusions [28][29][30].…”
Section: Introductionmentioning
confidence: 99%